«Top-Down» or «Bottom-Up»? : Social Participation, Agriculture and Mining in the Integrated Management of the Chancay-Lambayeque Watershed - Cano, Álvaro (2013)
The article assesses the institutionalization of social participation under the Integrated Water Resources Management (IWRM) model being implemented at the Chancay-Lambayeque watershed. First, it describes the bio-physical and social conditions at the basin; then, the evolution of national and local water institutions, from the Agrarian Reform to further decentralization and economicliberalization. Emphasizing the influence of the agricultural and mining sectors in these processes, four participatory mechanisms of the IWRM model are studied. The conclusions highlight: 1) the limited capacity of the central state to integrate a management in which the agricultural use is widely prevailing, and 2) the political challenge of promoting social participation in a context of conflict with the mining sector over the quality of the resource.